Study of steady-state thermal model for white light LEDs thermal management application at encapsulant level - Tran, Trong-Nam; Huynh, Van-Tuan; Vu, Thi-Hanh-Thu; Phan, Nguyet-Thuan; Nguyen , Huynh-Tuan-Anh; Nguyen, Quang-Khoi (Photonics Letters of Poland, 2024)
Thermal management for white LEDs at the encapsulant level is an important task to ensure that the device can operate at a high optical and color performance. In this study, a steady-state thermal model was built wherein the finite element method was employed using MATLAB software to identify the temperature distribution. The spatial temperature distribution of the encapsulant and blue LED die region was easily simulated and predicted. The obtained results are not only helpful in detecting the temperature behavior inside the packaging volume but also meaningful for designing the package configuration. Full Text: PDF References E.-F. Schubert, J.- K. Kim, "Solid-State Light Sources Getting Smart", Science, 308, 1274-1278 (2005). CrossRef Q.-K. Nguyen, "Emission spectrum modeling of white LEDs light source with using Gaussian function", Photonics Lett. Pol., 15, 54-56 (2023). CrossRef E. Schubert, Light-Emitting Diodes (2nd ed., Cambridge: Cambridge University Press, 2006). CrossRef C.-C. Sun, Q.-K. Nguyen, T.-X. Lee, S.-K. Lin, C.-S. Wu, T.-H. Yang, Y.-W. Yu, "Active thermal-fuse for stopping blue light leakage of white light-emitting diodes driven by constant current", Sci. Rep., 12, 12433 (2022). CrossRef Q.-K. Nguyen , B. Glorieux, G. Sebe , T.-H. Yang, Y.-W. Yu , C.-C. Sun, "Passive anti-leakage of blue light for phosphor-converted white LEDs with crystal nanocellulose materials", Sci. Rep. 13, 13039 (2023). CrossRef Q.-K. Nguyen, T.-P.-L. Nguyen, V.-T. Huynh, N.-T. Phan, and H.-T.-A. Nguyen, "An efficient decay model for studying the luminous flux behavior of phosphor-converted white light-emitting diodes", Photonics Lett. Pol., 15, 72-74 (2023). CrossRef J.- L. Davis, K.-C. Mills, G. Bobashev, K.-J. Rountree, M. Lamvik, R. Yaga, C. Johnson, "Understanding chromaticity shifts in LED devices through analytical models", Microelectron. Reliab., 84, 149-156 (2018). CrossRef M. Yazdan Mehr, A. Bahrami, W.-D. Van Driel, X.-J. Fan, J.- L. Davis, G.-Q. Zhang, "Degradation of optical materials in solid-state lighting systems", Int. Mater. Rev., 65, 102-128 (2020). CrossRef Su Y.-F., Yang S.-Y., Hung T.-Y., Lee C.- C., Chiang K.-N, "Light degradation test and design of thermal performance for high-power light-emitting diodes", Microelectron. Reliab., 52, 794-803 (2012). CrossRef K. Baran, M. Leśko, H. Wachta, and A. Różowicz, "Thermal modeling and simulation of high power LED module", AIP Conference Proceedings., 2078, 020048 (2019). CrossRef H.-K. Fu, C.-P. Wang, H.-C. Chiang, T.-T. Chen, C.-L. Chen, P.-T. Chou, "Evaluation of temperature distribution of LED module", Microelectron. Reliab., 53, 554-559 (2013). CrossRef M.-X. Chen, X. Chen, K. Xu, and L. Zheng, "Thermal simulation and analysis of flat surface flip-chip high power light-emitting diodes", J. Semicond., 34, (2013). CrossRef C.- M. Tan, P. Singh, W. Zhao, and H.-C. Kuo, "Physical Limitations of Phosphor layer thickness and concentration for White LEDs", Sci. Rep., 8, 2452 (2018). CrossRef F.P. Incropera, D.P. Dewitt. Fundamentals of Heat and Mass Transfer (Fifth Edition. New York: J. Wiley, 2002). DirectLink Q.-K. Nguyen, and T.-H.-T. Vu, "An Efficient Method for Simulating the Temperature Distribution in Regions Containing YAG:Ce3+ Luminescence Composites of White LED", J. Compos. Sci, 7, 301 (2023). CrossRef